Wear behavior of a microhybrid composite vs. a nanocomposite in the treatment of severe tooth wear patients: A 5-year clinical study. Issue 12 (December 2021) - Ning, K.; Bronkhorst, E.; Bremers, A.; Bronkhorst, H.; van der Meer, W.; Yang, F.; Leeuwenburgh, S.; Loomans, B.
Highlights: A standardized protocol to quantitatively evaluate composite restoration wear was developed. Nanocomposite restorations showed significantly less wear at bearing cusps. Microhybrid composite restorations showed less wear at non-bearing cusps and anterior maxillary teeth. Abstract: Objective: This study aimed to compare the wear behavior of a microhybrid composite vs. a nanocomposite in patients suffering from severe tooth wear. Methods: A convenience sample of 16 severe tooth wear patients from the Radboud Tooth Wear Project was included. Eight of them were treated with a microhybrid composite (Clearfil APX, Kuraray) and the other eight with a nanocomposite (Filtek Supreme XTE, 3M). The Direct Shaping by Occlusion (DSO) technique was used for all patients. Clinical records were collected after 1 month (baseline) as well as 1, 3 and 5 years post-treatment. The maximum height loss at specific areas per tooth was measured with Geomagic Qualify software. Intra-observer reliability was tested with paired t-tests, while multilevel logistic regression analyses were used to compare odds ratios (OR) of "large amount of wear". Results: Intra-observer reliability tests confirmed that two repeated measurements agreed well (p > 0.136). For anterior mandibular teeth, Filtek Supreme showed significantly less wear than Clearfil APX; in maxillary anterior teeth, Clearfil APX showed significantly less wear (OR material = 0.28, OR jaw position = 0.079, p < 0.001). For premolar and molar teeth, Filtek Supreme showed less wear in bearing cusps, whereas Clearfil APX showed less wear in non-bearing cusps (premolar: OR material = 0.42, OR bearing condition = 0.18, p = 0.001; molar: OR material = 0.50, OR bearing condition = 0.14, p < 0.001). Significance: Nanocomposite restorations showed significantly less wear at bearing cusps, whereas microhybrid composite restorations showed less wear at non-bearing cusps and anterior maxillary teeth.